Development of Muslim Identity Expression Scale - Ilmi Amalia; Hamdi Muluk; Mirra Noor Milla (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2023)
This study aimed to investigate the psychometric properties of Muslim identity expression scale, a measurement instrument used to evaluate various manifestations. Muslim identity obtained expressionin a multitude of domains, including the private sphere, politics, economics, socio-culture, legal matters, and education. The expression was categorized into two distinct functions, namely consolidation and mobilization. In the context of Indonesia, consolidation was defined as an expression that enhanced identity of individuals as Muslim. Meanwhile, mobilization changed the condition of Muslim, often related to power and politics, such as participating in political actions to defend Islam or supporting the establishment of political parties. This study comprised two distinct phases, namely the development of the scale and the examination of the structural validity. Based on a review of relevant literature and results from an open-ended questionnaire, 55 items were compiled and administered to 546 subjects. The results showed that 34 items met the criteria consisting of four dimensions, namely personal, interpersonal, collective action, and political participation expression. Confirmatory factor analysis (CFA) with 34 items and four dimensions matched the structure offered (ꭓ2 = 1793.805 df = 521, p < .01; RMSEA = 0.066, 90% CI = 0.062-0.069; CFI = 0.945; TLI = 0.94). The results provided preliminary evidence to support Muslim identity expression scale as a valid measuring tool with sound conceptual and empirical psychometric bases.